Effect of organic manures and site specific nutrient management practices (SSNM) in safflower (Carthamus tinctorius L.): EFFECT OF ORGANIC MANURES AND SSNM IN SAFFLOWER - C SUDHAKAR; C SUDHA RANI; K K K REDDY; T RAJESHWAR REDDY; S N C V L PUSHPAVALLI; K SANDYA RANI; P PADMAVATHI (Journal of Oilseeds Research, 2020)
A field experiment was conducted at the Agricultural Research Station, Tandur during 2014-15, 2015-16, 2016-17 and 2017-18 to evaluate the effect of FYM and site specific nutrient management (SSNM) practices in safflower. FYM was applied two weeks before sowing and fertilizers were applied to the crop based on uptake pattern, target yield and soil fertility status. The field trial was laid out in split plot design with four replications. In main plots two treatments were assigned viz., M1 - No manure, M2 - FYM @ 5 t/ha and five sub plots consisted of S1 - Control (No fertilizer), S2 - Recommended NPK, S3- SSNM (STCR equation) for target yield of 1.5 t/ha, S4- S3 + micronutrients (Zn @ 5 kg/ha + S @ 10 kg/ha), S5 - S3 + if soil is deficient add 25% more than S2, if soil is medium apply as S2 and if soil is high apply 25% less than S2. Application of FYM @ 5 t/ha (M2) resulted in significantly higher plant height (105.89 cm), primary branches (10.14), number of capitula (30.14), seed weight/plant (9.40 g), 100 seed weight (6.42 g), dry weight/plant (58.92 g), Seed yield (1377 kg/ha), biological yield (5862 kg/ha), harvest index (20.16%) and gross returns (`39626/ha). However, net returns (`16669/ha) and B:C ratio (2.00) was higher in no manure application. Application of fertilizers based on S4- SSNM (STCR equation) for targeted yield of 1.5 t/ha + micronutrients (Zn @ 5 kg/ha + S @ 10 kg/ha) recorded significantly higher plant height (115.07 cm), primary branches (12.23), number of capitula/plant (36.33), seed weight/plant (11.28 g), 100 seed weight (6.54 g), dry weight/plant (64.47 g), seed yield (1650 kg/ha), biological yield (6227 kg/ha), harvest index (21.81 %), gross returns (` 47511 /ha) and net returns (` 20881 /ha).